Are loneliness and social network size mediators between childhood adversity and depressive symptoms? A cross-sectional replication study in Ethiopia - Mubarek Abera; Kristina Adorjan; Benedikt L Amann; Paula Gerbig; Matthias Alexander Reinhard; Henok Ababu; Stephanie Rek; Frank Padberg; Andrea Jobst (BMJ Open)
Introduction Loneliness and adverse childhood experiences (ACEs) constitute significant risk factors for mental disorders, with loneliness emerging as a serious global public health concern. Recent research highlights the role of loneliness as a potential link between early life adversities and current psychopathology. However, most studies have been conducted in high-income, highly individualistic countries. This cross-sectional study explores the interplay between loneliness, social network size, recalled ACEs and depressive symptoms in Ethiopia—a low-income and collectivistic cultural context.Methods The study included 125 psychiatric outpatients at Jimma University Medical Center in Southwest Ethiopia diagnosed with major depressive disorder, bipolar disorder or psychotic disorders, as well as 131 non-clinical participants. Trained interviewers administered the University of California, Los Angeles (UCLA) Loneliness Scale, the Childhood Trauma Questionnaire, the Social Network Index and the WHO-5 Well-Being Index. We used Mann-Whitney U tests, partial correlation and mediation analysis for data analysis.Results We found mild-to-moderate correlations between loneliness and ACEs (clinical group: rho=0.29, p<0.001, 95% CI (0.13 to 0.45); non-clinical group: rho=0.42, p<0.001, 95% CI (0.27 to 0.56)). In both groups, loneliness fully mediated the association between ACEs and depressive symptoms (clinical group: indirect effect a1b1=0.07, 95% CI (0.02 to 0.13); non-clinical group: indirect effect a1b1=0.03, 95% CI (0.01 to 0.07)). In contrast, social network size was neither correlated with ACEs nor did it mediate the association between ACEs and depressive symptoms in either group.Conclusion This study replicates previous findings that loneliness—rather than social network size—is associated with ACEs and mediates their impact on depressive symptoms. These results support the transcultural and transdiagnostic relevance of loneliness as a universal psychological mechanism, independent of societal structure.